Preparation of Oil-Encapsulated Microcapsules and Tribological Property of Ni Composite Coating. Issue 1 (2nd January 2016) - Aruna, S. T.; Arunima, S.; Latha, S.; William Grips, V. K.
Abstract : Microcapsules containing oil are potential candidate materials for preparing electrocomposite coatings with excellent tribological properties. In the present study, the preparation of oil-encapsulated microcapsules and electrodeposition of Ni-microcapsule composite coating are presented along with the properties of the coating. In situ interfacial polymerization method was used for the preparation of lubricating oil-encapsulated urea-formaldehyde microcapsules. The synthesized microcapsules were incorporated into the nickel matrix by electrodeposition using Ni-Watts bath. The Ni-composite coating containing microcapsules exhibited smaller Ni grain size, higher microhardness and lower surface roughness compared to plain Ni coating. Electrodeposited Ni coating containing oil-encapsulated microcapsules exhibited improved tribological properties with lower wear loss and coefficient of friction compared to plain nickel coating.